(untitled) (Jurnal Destinasi Pariwisata, 2025)
The knowledge gap of the younger generation and tourists regarding ceremonial plants, as well as the threat of crop scarcity and erosion of traditional knowledge, encourages the need to develop an integrative tourism model. The formulation of the research problem is how to formulate a tourism product model based on the introduction of Yadnya ceremonial plants that are effective and sustainable in the village. This study uses a mixed-methods approach with in-depth interview data collection techniques, participatory observation, and literature study. The data is analyzed thematically and uses SWOT analysis to formulate a development strategy. The results of the research designed an educational tour package "The Spiritual Journey of Plants" consisting of a Guided Ethnobotanical Tour and a Hands-on Offering Workshop. This model leverages local strengths such as traditional knowledge and beautiful environments, and integrates revenue sharing mechanisms for conservation funds to ensure sustainability. The findings of the study show that this model not only creates unique and immersive tourism products, but also becomes a community-based in-situ conservation strategy that directly engages tourists in the preservation of botanical-ethnographic knowledge and ceremonial plants.